Microstructural scale strain localisation in nuclear graphite - Joyce, MR; Marrow, T (2008)
The surface strain fields evolved during disc compression tests on virgin IM1-24 were obtained via electronic speckle pattern interferometry (ESPI). A methodology for characterising strain localisation on a microstructural scale is presented, which provides a quantitative description of the damage localisation and failure processes. © 2008.